PKM Workshop Pembuatan Lembar Kerja Peserta Didik (LKPD) - Panjaitan, Ruqiah Ganda Putri; Indrayani, Yuliati; Utomo, Kiki Prio; Hiendro, Ayong; Hendri, M. Irfani (LPPM Universitas Pamulang, 2023)
Today's 21st century learning requires students and teachers to be able to adapt, have critical thinking skills, have the ability to solve problems, be able to communicate and collaborate, as well as be creative and innovative. In the 21st century learning does not only rely on knowledge but also skills. However, in reality this has not met expectations. To achieve appropriate knowledge and skills, teaching materials used by teachers should be accompanied by Student Activity Sheets (LKPD). However, there are indications that teachers have problems in preparing LKPD because most teachers do not understand how to bring up 21st century skills. The LKPDs developed are also not in accordance with learning models and methods for applying 21st century skills. Thus the LKPD making workshops conducted aim to shape teacher abilities in making good and interesting LKPD with the aim of making the learning process more qualified. The method used is socialization, various lectures consisting of delivery of material, questions and answers and discussions, as well as the practice of making LKPD accompanied by the implementing team. Workshop participants were teachers of SD Negeri 18 North Pontianak. The result of this workshop activity is that teachers understand the components that must be in LKPD, understand the steps for preparing LKPD, and are able to produce one LKPD product.